Rapid Enlargement of Aneurysmal Remnant as a Cause of Early Rebleed after Coil Embolization of Posterior Communicating Artery Aneurysm: A Case Report - Ambekar, Sudheer; Banerjee, Anirban Deep; Chittiboina, Prashant; Cuellar-Saenz, Hugo; Sin, Anthony; Nanda, Anil (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Early rebleeding of an aneurysm following endovascular coiling is a serious complication and carries a high risk of mortality and morbidity.Clinical Presentation A 56-year-old woman was diagnosed with subarachnoid hemorrhage (SAH) due to rupture of a saccular aneurysm arising from the communicating segment (PComm) of the right internal carotid artery. She underwent an uneventful right pterional craniotomy and clipping of the aneurysm. On postoperative day 5, she lapsed into altered sensorium. Computed tomography (CT) of the head showed fresh subarachnoid bleed and digital subtraction cerebral angiography (DSA) demonstrated a relatively small (4.9 mm × 3.5 mm × 2.6 mm) left PComm saccular aneurysm with complete obliteration of the previously clipped right PComm aneurysm. She underwent coil embolization of this aneurysm, with a small remnant at the neck (>95% occlusion was achieved). On postcoiling day 9, she again lapsed into altered sensorium. CT of the head revealed fresh SAH. CT-angiography and DSA was performed, which showed significant enlargement of the residual left PComm aneurysm with coil impaction.Intervention Patient was subjected to a standard left pterional craniotomy and clipping of the residual aneurysm. She also underwent a subsequent ventriculoperitoneal shunt for the associated hydrocephalus. She gradually recovered and was able to return to work with minimal disability.Conclusion Rapid enlargement and rupture of an aneurysmal remnant following endovascular coiling is a rare cause of an early rebleed, especially associated with “small” aneurysms. A more stringent postprocedural imaging strategy along with restrained anticoagulation in such “high-risk” cases is recommended.
Keywords: pseudoaneurysm; rupture; rebleeding; coil embolization